Analysis of effect of physical parameters on the performance of lead acid battery as efficient storage unit in power systems using new finite-element-method-based model. (March 2022) - Rajamand, Sahbasadat
Highlights: Analysis of three dynamic models based on charging/discharging status. Using FEM-based model and dynamic equations. Temperature-behavior analysis of the proposed model of lead acid battery. Analysis of charging/discharging rate versus the main parameters as temperature, voltage and current. Abstract: Batteries are known as energy storage units relating between generators and consumers. From known batteries, Lead acid battery is attentional because of low cost, charging/discharging rate and efficiency while it is widely used in technical systems. Due to the complexity of the structure of lead acid battery, modeling and simulation of this element can be useful to diagnose its behavior and details of analysis in view of charging process, thermal effect and performance. In this paper, a new Finite-Element-Method (FEM)-based model using energy equations is proposed where simulation is done to present the performance of this battery in different conditions. The effect of temperature in charging/discharging rate is also analyzed. The efficiency of lead acid battery based on the proposed model is shown in the simulation results. In addition, the analysis of cycle number, capacity and charging/discharging process is presented to provide clearer explanation of this battery behavior. As shown in simulation results, self discharging is low and using low thermal flow mode, power loss of the battery is reduced which leads to more efficiency and more stable current and voltage in the battery output port.